Caracterização físico-mecânica de misturas de solo-cimento autoadensável com incorporação de areia de resíduos de construção civil - Simioni, Fernanda Cavatti (2019)
The significant environmental impacts caused by mineral extraction have forced the construction industry to study new concepts and technical solutions in order to create more ecological and sustainable activities. Self-compacting soil-cement containing recycled aggregates is characterized as a mixture of soil, water, cement and a superplasticizer additive, with sufficient fluidity to mold walls and structural elements without the need for mechanical densification. In this context, the aim of this study is to analyze the influence of partial sand incorporation from Civil Construction Residues (CCR) to Self-Adhesive Cement (SAC) mixtures, both in the fresh and hardened state, in order to develop a suitable trace for the manufacture of monolithic walls. The following inputs were used as mixture components: soil, cement, water, a superplasticizer additive and CCR sand. Fresh spreading, funnel and segregation, mass density and air content assays were carried out. In the hardened state, simple compressive strength tests (7, 14 and 28 days), water absorption, capillary absorption and void index assessments were performed, using standard 50x10mm proof specimens. The assays indicate that the CCR sand incorporation percentages of 25% and 50% to the mixtures in the fresh state led to workability and flowability improvements, with visual stability and no segregation or exudation. In the hardened state, CCR sand incorporation led to increased mechanical mixtures strength in relation to the reference trace, with the highest strength achieved at 25% CCR sand incorporation. With the exception of the 10% CCR sand mixture, no statistical differences were observed between the assessed mixtures (p <0.05). CCR sand incorporation also aided in reducing water absorption, leading to values below 20%, especially for the 25% incorporation mixture, which presented the lowest water absorption. It is concluded, therefore, that the incorporation of CCR sand in the mixtures resulted in SAC mixture performance characteristic improvements, enhancing their use for applications to monolithic walls